Cofactor squelching: Artifact or fact?. (7th June 2016) - Schmidt, Søren Fisker; Larsen, Bjørk Ditlev; Loft, Anne; Mandrup, Susanne
Abstract : Cofactor squelching is the term used to describe competition between transcription factors (TFs) for a limited amount of cofactors in a cell with the functional consequence that TFs in a given cell interfere with the activity of each other. Since cofactor squelching was proposed based primarily on reporter assays some 30 years ago, it has remained controversial, and the idea that it could be a physiologically relevant mechanism for transcriptional repression has not received much support. However, recent genome‐wide studies have demonstrated that signal‐dependent TFs are very often absent from the enhancers that are acutely repressed by those signals, which is consistent with an indirect mechanism of repression such as squelching. Here we review these recent studies in the light of the classical studies of cofactor squelching, and we discuss how TF cooperativity in so‐called hotspots and super‐enhancers may sensitize these to cofactor squelching. Abstract : Cofactor squelching describes the competition between transcription factors (TFs) for a limited amount of cofactors in the cell. Here we review recent genome‐wide studies supporting cofactor squelching as a general mechanism of repression and discuss how TF cooperativity in so‐called hotspots and super‐enhancers may sensitize these to cofactor squelching.